A-SATMVSNet: An attention-aware multi-view stereo matching network based on satellite imagery - Lin, Li; Zhang, Yuanben; Wang, Zongji; Zhang, Lili; Liu, Xiongfei; Wang, Qianqian (Frontiers in Earth Science, 2023)
The stereo matching technology of satellite imagery is an important way to reconstruct real world. Most stereo matching technologies for satellite imagery are based on depth learning. However, the existing depth learning based methods have the problems of holes and matching errors in stereo matching tasks. In order to improve the effect of satellite image stereo matching results, we propose a satellite image stereo matching network based on attention mechanism(A-SATMVSNet). To solve the problem of insufficient extraction of surface features, a new feature extraction module based on triple dilated convolution with attention module is proposed, which solves the problem of matching holes caused by insufficient extraction of surface features. At the same time, compared with the traditional weighted average method, we design a novel cost-volume method that integrates attention mechanism to reduce the impact of matching errors to improve the accuracy of matching. Experiments on public multi-view stereo matching dataset based on satellite imagery demonstrate that the proposed method significantly improves the accuracy and outperforms various previous methods. Our source code is available at https://github.com/MVSer/A-SATMVSNet.